2009
DOI: 10.1186/1472-6890-9-11
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical and other prognostic factors in B cell non Hodgkin lymphoma patients, Kampala, Uganda

Abstract: BackgroundNon Hodgkin lymphomas are the most common lymphomas in Uganda. Recent studies from developed countries have shown differences in survival for the different immunophenotypes. Such studies are lacking in Africa where diagnosis is largely dependent on morphology alone. We report immunohistochemical and other prognostic factors in B cell non Hodgkin lymphoma patients in Kampala, Uganda.MethodsNon Hodgkin lymphoma tissue blocks from the archives of the Department of Pathology, Makerere University College … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…In resource-rich settings, these have included the tumor stage, bulk and histopathologic type, age, serum lactate dehydrogenase (LDH) level, performance status, and the number of nodal and extra nodal sites involved 12–14. Receipt of both chemotherapy and supportive therapy (e.g., Granulocyte colony-stimulating factor, G-CSF) has also influenced treatment outcomes 15–17.…”
Section: Introductionmentioning
confidence: 99%
“…In resource-rich settings, these have included the tumor stage, bulk and histopathologic type, age, serum lactate dehydrogenase (LDH) level, performance status, and the number of nodal and extra nodal sites involved 12–14. Receipt of both chemotherapy and supportive therapy (e.g., Granulocyte colony-stimulating factor, G-CSF) has also influenced treatment outcomes 15–17.…”
Section: Introductionmentioning
confidence: 99%
“…Diffuse large B‐cell lymphoma (DLBCL) is the commonest NHL subtype in SSA, as in other parts of the world (Naresh et al , ). Previous reports from SSA have largely consisted of retrospective studies with non‐standardized patient evaluation and treatment, and high loss to follow‐up (Wood et al , ; Mwanda et al , ; Tumwine et al , ; Bateganya et al , ; de Witt et al , ; Sissolak et al , ; Milligan et al , ).…”
mentioning
confidence: 99%
“…52 In contrast, Tumwine et al 62 found that activated germinal center DLBCL, defined as those expressing CD10, Bcl-6, MUM1 and CD138, was associated with superior survival outcome. In the present study, statistic observation revealed that CD138 expression in >25% of tumour cells (score ≥2), occurred only in the HIV positive group and was associated with shorter survival time.…”
Section: Survival Functionsmentioning
confidence: 97%
“…53 The common morphologic variants of DLBCL include centroblastic, immunoblastic and anaplastic variants. Chang et al, 59 Madan et al 60 found that the immunophenotype in AIDS-related It is noteworthy that in one of few studies to emerge from Africa, specifically Uganda, Tumwine et al 62 established that the activated germinal center-type DLBCL, defined as those expressing CD10, Bcl-6, MUM1 and CD138, was found to have the best prognosis relative to other groups of DLBCL in their study.…”
Section: Morphologic Subtypes Of Dlbclmentioning
confidence: 99%